Analisis Penyajian Akun Pendapatan Diterima di Muka Dari Pelayanan Pertanahan Pada Laporan Keuangan Kementerian Agraria dan Tata Ruang/Badan Pertanahan Nasional Tahun 2022 dan 2023 - Pranata, Moch. Noer Ali Tedi; Budi Y, Harti (Magister Ilmu Akuntansi Universitas Jambi, 2024)
This study aims to analyze the presentation of Land Services Unearned Revenue in the Financial Statements of the Ministry of Agrarian Affairs and Spatial Planning / National Land Agency in 2022 and 2023 and its conformity with Government Accounting Standards. Within the scope of the public sector, PDDM is a government obligation that arises because the government has received resources, but the government has not yet delivered goods/services to third parties. In 2022 and 2023, the recognition, valuation, presentation of Unearned Revenue from land services carried out within the Ministry of ATR/BPN was not fully in accordance with the Central Government Accounting Policy which, among others, stipulates that Unearned Revenue is recognized when cash has been received by the government from third parties, but there has been no delivery of goods/services from the government as of the reporting date. This resulted in a potential misstatement of Unearned Revenue Account in the Unaudited Balance Sheet of the Ministry of ATR / BPN in 2022 and 2023.